Kualitas Gel Pengharum Ruangan Berbahan Dasar Karagenan dan Tepung Sagu dengan Pewangi Jeruk Purut: Quality of Gel Fragrance Made of Carrageenan and Sago Flour Scented by Kaffir Lime - Raja Bonan Dolok Sormin; Adrianus O.W. Kaya; Jemris Maahury (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
Everyone needs a comfortable room atmosphere for carrying out activities. For this purpose, air freshener is used. An air freshener that is good for health is an air freshener with natural ingredients. Currently, air freshener in the form of gel is being manufactured for some reason were not spilling, the fragrance is longer binding, easy to use, elastic, and the design easily created. This study aims to make the gel air freshener with a combination of carrageenan and sago starch as a gelling agent and using kaffir lime oil as a fragrance. The research method was the application of a ratio of carrageenan powder and sago powder by 3: 1 and kaffir lime oil concentrations of 0.5%, 1%, and 1.5%. Gelling air freshener with a combination of carrageenan and sago starch as a gelling agent and kaffir lime oil as a fragrance with a concentration of 1.5%, and 1% resulted in the same or the smallest syneresis value and then a concentration of 1.5% had a total evaporation of the liquid in a small number, residual gel weight in a large number, the retention in a large number, and its release in a small number, compared to other treatments, hence, a room freshener by concentration of 1.5% was the best treatment.